Multilevel transition in empty substrate integrated waveguide. Issue 18 (1st September 2016) - Morro, J.V.; Rodríguez, A.; Belenguer, A.; Esteban, H.; Boria, V.
Abstract : Empty substrate integrated waveguide (ESIW) is an improvement of the well‐known substrate integrated waveguide. While maintaining the low cost, easy manufacturing, small size, and integration with other circuits in the same substrate, ESIW decreases the related losses by removing the dielectric substrate, thus rendering it more interesting for practical applications. A wide band transition has been already developed to connect ESIW to microstrip lines. Filters, couplers, and antennas have also been developed in ESIW. For multilevel configurations, where different ESIW devices are implemented in different stacked substrates, a transition is needed that connects ESIW lines in different substrate levels. A low reflection wideband transition is presented for connecting two stacked ESIW lines.